2016
DOI: 10.1007/s12161-016-0583-6
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Six Phthalates and One Adipate in Luxembourgish Beer Using HS-SPME-GC/MS

Abstract: A simple, low-cost and sensitive method for the determination of six phthalate acid esters (dimethyl phthalate, diethyl phthalate, dibutyl phthalate, benzyl butyl phthalate, bis(2-ethylhexyl) phthalate and dioctyl phthalate) and one adipate (bis(2-ethylhexyl) adipate) in beer has been developed using head-space solid-phase microextraction (HS-SPME) followed by gas chromatography coupled to mass spectrometry (GC/MS). SPME conditions were optimised, and optimum extraction parameters were found to be 95°C at 100 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
26
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 36 publications
(52 reference statements)
4
26
4
Order By: Relevance
“…Mean and median concentrations of DEHP in beverages were 1.60 ng g −1 and 0.62 ng g −1 , respectively . Similar findings were shown by Carnol et al ., who reported that DBP and DEHP levels were about 0.05 μg L −1 to 37.14 μg L −1 and 1.01 μg L −1 to 61.56 μg L −1 , respectively, in Luxembourgish breweries . Selecting packaged food materials in larger plastic containers that are thicker and kept at temperatures below 4 °C and refraining from reusing plastic containers can minimise the migration phenomenon.…”
Section: Resultsmentioning
confidence: 99%
“…Mean and median concentrations of DEHP in beverages were 1.60 ng g −1 and 0.62 ng g −1 , respectively . Similar findings were shown by Carnol et al ., who reported that DBP and DEHP levels were about 0.05 μg L −1 to 37.14 μg L −1 and 1.01 μg L −1 to 61.56 μg L −1 , respectively, in Luxembourgish breweries . Selecting packaged food materials in larger plastic containers that are thicker and kept at temperatures below 4 °C and refraining from reusing plastic containers can minimise the migration phenomenon.…”
Section: Resultsmentioning
confidence: 99%
“…SPE or SPME has been used in the analysis of beer for BPA and benzene, trihalomethanes, and formaldehyde (Cao et al., 2010; Wu et al., 2006). Specifically for GC procedures, direct headspace extraction, headspace SPE, or SPME may be used, which has been used frequently for processing contaminants in wine, beer, and Korean liquors (Bogdanova et al., 2018; Ferreira et al., 2018; Hernandes et al., 2020; Lago et al., 2017; Ryu et al., 2015), as well as for methanol in various alcohols and phthalates in beer (Carnol et al., 2017; Destanoğlu & AteŞ, 2019). The QuEChERS method is commonly employed for pesticides and incorporates liquid–liquid extraction and dispersive SPE techniques, and may be used prior to GC analysis of wine (Słowik‐Borowiec & Szpyrka, 2018), and has also been utilized for phthalates in baijiu liquor (Dong et al., 2019).…”
Section: Methodsmentioning
confidence: 99%
“…Phthalates have been shown in multiple studies to be capable of migrating into aqueous and slightly nonpolar solutions, in both instances of food simulants and actual products (Biscardi et al., 2003; Bosnir et al., 2007; Fasano, Bono‐Blay, Cirillo, Montuori, & Lacorte, 2012; Gärtner, Balski, Koch, & Nehls, 2009; Jurica et al., 2016; Moreira, André, & Cardeal, 2013). Several phthalates types such as DEHP, DBP, and DEP have been detected in beer, wine, and spirit samples, with notably higher concentrations in distilled alcohol products (Cao, 2010; Carnol, Schummer, & Moris, 2017; Chatonnet et al., 2014; Pang et al., 2017). There has been concern raised over the possible migration of phthalates and adipates from cheaper cork substitutes into wines; though the presence of such contaminants has been reported in wines, thus far it has not been conclusively demonstrated to stem from this specific source (Sendon et al., 2012).…”
Section: Types Of Contaminants In Alcoholic Beveragesmentioning
confidence: 99%
“…In aluminium cans and bottles phthalates may originate from the polymer coating covering the aluminium inside the bottle or can. The alcohol content in beer may aid in releasing the phthalate into beer (Ye et al, 2009;Carnol et al, 2017;Olšovská et al, 2019).…”
Section: Beermentioning
confidence: 99%